WIRELESS DATA COLLECTION SYSTEM ON FPGA FOR FREQUENCY CONVERTERS OF PHYSICAL QUANTITIES USING LORA - OSADCHUK, OLEKSANDR; SKOSHCHUK, VALENTYN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study presents a system for collecting and transmitting measurements from a multichannel radio engineering system based on FPGA for frequency converters of physical quantities using the LoRa protocol. To implement this system, the development of a measurement collection device was completed, and a hub capable of receiving data from several such devices was created. The hub is built on the Lilygo LORA32 module, enabling the accumulation of measurements in a single point with subsequent transmission via wireless communication channels, including WiFi and Bluetooth. The proposed approach is based on the use of the Lilygo LORA32 module to create a multichannel measurement system that combines the advantages of high-performance computing platforms with wireless data transmission capabilities. The primary goal of the development is to ensure reliable collection, processing, and transmission of measurements in systems with frequency sensors of physical quantities. This was achieved through the development of a data transmission protocol in a compact CBOR format and the integration of LoRa technology. The developed system represents an important step toward the creation of modern measurement platforms characterized by high accuracy, reliability, and wireless data transmission capabilities. Further development of the platform involves the implementation of new data processing methods, improved hub performance, and the creation of integrated solutions for real-time monitoring. This opens up opportunities for the broad application of the system in IoT, industrial automation, environmental monitoring, and many other fields.
Keywords: LILYGO LoRa32; NIOS II; FPGA; multichannel frequency meter; sensor with frequency output; radio measuring transducers of physical quantities; frequency